PMMA-Based Continuous Hemofiltration Modulated Complement Activation and Renal Dysfunction in LPS-Induced Acute Kidney Injury - Stasi, Alessandra; Franzin, Rossana; Divella, Chiara; Sallustio, Fabio; Curci, Claudia; Picerno, Angela; Pontrelli, Paola; Staffieri, Francesco; Lacitignola, Luca; Crovace, Antonio; Cantaluppi, Vincenzo; Medica, Davide; et al. (Frontiers in Immunology, 2021)
Sepsis-induced acute kidney injury (AKI) is a frequent complication in critically ill patients, refractory to conventional treatments. Aberrant activation of innate immune system may affect organ damage with poor prognosis for septic patients. Here, we investigated the efficacy of polymethyl methacrylate membrane (PMMA)-based continuous hemofiltration (CVVH) in modulating systemic and tissue immune activation in a swine model of LPS-induced AKI. After 3 hours from LPS infusion, animals underwent to PMMA-CVVH or polysulfone (PS)-CVVH. Renal deposition of terminal complement mediator C5b-9 and of Pentraxin-3 (PTX3) deposits were evaluated on biopsies whereas systemic Complement activation was assessed by ELISA assay. Gene expression profile was performed from isolated peripheral blood mononuclear cells (PBMC) by microarrays and the results validated by Real-time PCR. Endotoxemic pigs presented oliguric AKI with increased tubulo-interstitial infiltrate, extensive collagen deposition and glomerular thrombi; local PTX-3 and C5b-9 renal deposits and increased serum activation of classical and alternative Complement pathways were found in endotoxemic animals. PMMA-CVVH treatment significantly reduced tissue and systemic Complement activation limiting renal damage and fibrosis. By microarray analysis, we identified 711 and 913 differentially expressed genes with a fold change >2 and a false discovery rate <0.05 in endotoxemic pigs and PMMA-CVVH treated-animals, respectively. The most modulated genes were Granzyme B, Complement Factor B, Complement Component 4 Binding Protein Alpha, IL-12 and SERPINB-1 that were closely related to sepsis-induced immunological process. Our data suggest that PMMA-based CVVH can efficiently modulate immunological dysfunction in LPS-induced AKI.